Spatiotemporal distribution of the glycoprotein pherophorin II reveals stochastic geometry of the growing ECM of Volvox carteri - Benjamin von der Heyde; Anand Srinivasan; Sumit Kumar Birwa; Eva Laura von der Heyde; Steph S. M. H. Höhn; Raymond E. Goldstein; Armin Hallmann (Proceedings of the National Academy of Sciences, 2025)
The evolution of multicellularity involved the transformation of a simple cell wall of unicellular ancestors into a complex, multifunctional extracellular matrix (ECM). A suitable model organism to study the formation and expansion of an ECM during ontogenesis is the multicellular green alga Volvox carteri , which, along with the related volvocine algae, produces a complex, self-organized ECM composed of multiple substructures. These self-assembled structures primarily consist of hydroxyproline-rich glycoproteins, a major component of which is pherophorins. To investigate the geometry of the growing ECM, we fused the yfp gene with the gene for pherophorin II (PhII) in V. carteri . Confocal microscopy reveals PhII:YFP localization at key ECM structures, including the boundaries of compartments surrounding each somatic cell and the outer surface of the organism. Image analysis during the life cycle allows the stochastic geometry of growing compartments to be quantified; their areas and aspect ratios exhibit robust gamma distributions and exhibit a structural transition from a tight polygonal to a looser acircular packing geometry with stable eccentricity over time, evoking parallels and distinctions with the behavior of hydrated foams. These results provide quantitative insight into a general, open question in biology: how do cells collectively produce a complex structure external to themselves in a robust and accurate manner?